Chitosan nanoparticle applications in dentistry: a sustainable biopolymer - Mascarenhas, Roma; Hegde, Shreya; Manaktala, Nidhi (Frontiers in Chemistry, 2024)
The epoch of Nano-biomaterials and their application in the field of medicine and dentistry has been longlived. The application of nanotechnology is extensively used in diagnosis and treatment aspects of oral diseases. The nanomaterials and its structures are being widely involved in the production of medicines and drugs used for the treatment of oral diseases like periodontitis, oral carcinoma, etc. and helps in maintaining the longevity of oral health. Chitosan is a naturally occurring biopolymer derived from chitin which is seen commonly in arthropods. Chitosan nanoparticles are the latest in the trend of nanoparticles used in dentistry and are becoming the most wanted biopolymer for use toward therapeutic interventions. Literature search has also shown that chitosan nanoparticles have anti-tumor effects. This review highlights the various aspects of chitosan nanoparticles and their implications in dentistry.